Mapeamento da macrófita invasora Hedychium coronarium J. Köenig (Zingiberaceae) e como a ciência cidadã contribui para o registro desta espécie no estado de São Paulo - Roque, Beatriz de França (2023)
Biological invasion is recognized as one of the main causes of biodiversity loss. Among the main invasive species in Brazil is Hedychium coronarium, an amphibious and perennial macrophyte from humid environments, for which there is insufficient information on the factors that favor its invasion. Citizen Science is used, as society participates in scientific research on the importance and preservation of biodiversity. Environmental monitoring carried out in conjunction with society helps to detect problems that the species causes and allows them to be resolved in advance, when it is still a viable process. Thus, the work was developed from two perspectives. The first aimed to evaluate the occurrence and estimate the level of invasion of the invasive species within Conservation Units in the state of São Paulo. The field research considered 29 visits, covering perimeters with invasions and recording them with the help of the iNaturalist application over a period of one year. Based on the results obtained in this research, the invasive species had a greater distribution in areas of Dense Ombrophylous Forest, even far from water bodies, while in areas of Semideciduous Seasonal Forest and Cerrado it only occurred in areas closer to the water body. The second aimed to describe the use of the iNaturalist application as a Citizen Science tool, used to monitor invasive species in the state of São Paulo and promote the adoption of this application among various members of society. Data collection was carried out from May 2022 to July 2023. From this project, workshops and workshops were given by research professors on biological invasions and the iNaturalist application was presented. From this study, a total of 794 records of the species were obtained, 221 of which were made by members external to the project. In relation to the number of observers, there was an increase of 98 registered, all members external to the project. These values result in the partnership between research and the public and allow us to infer that society was very participative in the project. This research, with the proposed methods and respective positive results achieved, supports current scientific technical efforts in Protected Areas and Conservation Units. The purpose is to meet the need for identification and immediate response to several other invasive species, as well as serving as an example for the development of Citizen Science actions on issues related to biodiversity.